Kontribusi Guru Kelas dalam Pembinaan Kode Etik Siswa MIN di Kota Banda Aceh - Mardiana Mardiana; Syabuddin Gade (DAYAH: Journal of Islamic Education, 2019)
Developing students’ code of ethics is part of the main duties and functions of teachers as educators and instructors in schools. The study of this thesis aimed to investigate the socialization ways of the students’ code of ethics, the methods used in developing the students’ code of ethics, and the obstacles indeveloping the students’ code of ethics faced by thehomeroomteachers of MIN (Islamic elementary schools) in Banda Aceh downtown. This study used a descriptive qualitative research design. Data collection techniques included observation, interview, and documentation study. The subjects of the study were the principals and the homeroom teachers of MIN 4, MIN 5, and MIN 6 in Banda Aceh. The results of the study showed that first, the principals and the homeroom teachers have always tried to socialize the students’code of ethics, either through the preparation of the program at the beginning of the school year or through the pamphlets displayed in places seen by everyone in the schools. In addition, the teachers have made an agreement with the students by listing some violations and rewards in the classrooms. All of these aimed to foster the students’code of ethics in order to improve the quality of character education at MIN Banda Aceh. Second, the homeroom teachers applied persuasive and educativemethods and techniquesin fostering the code of ethics for the students. These werecarried out by distributing brochures at the beginning of the school year for the first year students, creating an educational slogan, and putting the school code of ethics on pamphlets. The other methods used were being role models, direct reprimanding, providing suggestions for more polite and respectful attitudes, communicating effectively, and giving rewards and educative sanctions. And third, the obstacles encountered by the teachers in the development of the students’ code of ethics included the lack of religious education in the family, limited time for the teachers to conduct optimal supervision on the code of ethics for the students, the size of the classroom, and the immature age of the students. However, the teachers have made efforts to overcome allof these obstacles properly. If there are some issues related to the students’ code of ethics, they will make appropriate measures in order to reduce the obstacles.